A dead-beat control for bridgeless inverter systems to reduce the distortion of grid current - Lee, June Hee; Lee, Kyo Beum (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2018)
This paper proposes a method to reduce the distortion of the grid current using a dead-beat control (DBC) scheme for bridgeless inverter systems. In the case of the general proportional integral (PI) current controller for power factor correction (PFC) scheme, the grid current is generally distorted due to the slow dynamic response of the PI controller. If the bandwidth of the PI controller increases to overcome this characteristic, the system shows a fast dynamic response. However, it becomes unstable as wide bandwidth leads to the control of unnecessary values such as a grid current noise. On the contrary, the proposed PFC-DBC method has a fast response for the reference current and accuracy compared to the conventional PFC-PI method owing to the optimal duty cycle for the next state current. In addition, the proposed PFC-DBC method can operate robust control by using the estimation method for actual filter inductance. Therefore, the proposed method can reduce the grid current distortion. The proposed method is verified through powersim simulations and experiments.
Keywords: Bridgeless inverter; Deadbeat control; Model based controls; Power factor control; Power inverters; Bridgeless inverter; Dead-beat control (DBC); Model-based control (MBC); Power factor control (PFC); Small power inverter